Subjective and Objective Measures of Dryness Symptoms in Primary Sjögren's Syndrome: Capturing the Discrepancy. Issue 11 (9th October 2017) - Bezzina, Oriana M.; Gallagher, Peter; Mitchell, Sheryl; Bowman, Simon J.; Griffiths, Bridget; Hindmarsh, Victoria; Hargreaves, Ben; Price, Elizabeth J.; Pease, Colin T.; Emery, Paul; Lanyon, Peter; Bombardieri, Michele; et al.
Abstract : Objective: To develop a novel method for capturing the discrepancy between objective tests and subjective dryness symptoms (a sensitivity scale) and to explore predictors of dryness sensitivity. Methods: Archive data from the UK Primary Sjögren's Syndrome Registry (n = 688) were used. Patients were classified on a scale from −5 (stoical) to +5 (sensitive) depending on the degree of discrepancy between their objective and subjective symptoms classes. Sensitivity scores were correlated with demographic variables, disease‐related factors, and symptoms of pain, fatigue, anxiety, and depression. Results: Patients were on average relatively stoical for both types of dryness symptoms (mean ± SD ocular dryness −0.42 ± 2.2 and −1.24 ± 1.6 oral dryness). Twenty‐seven percent of patients were classified as sensitive to ocular dryness and 9% to oral dryness. Hierarchical regression analyses identified the strongest predictor of ocular dryness sensitivity to be self‐reported pain and that of oral dryness sensitivity to be self‐reported fatigue. Conclusion: Ocular and oral dryness sensitivity can be classified on a continuous scale. The 2 symptom types are predicted by different variables. A large number of factors remain to be explored that may impact symptom sensitivity in primary Sjögrenʼs syndrome, and the proposed method could be used to identify relatively sensitive and stoical patients for future studies.